Activation of TRPV1 Prevents OxLDL-Induced Lipid Accumulation and TNF-α-Induced Inflammation in Macrophages: Role of Liver X Receptor α. (25th June 2013) - Zhao, Jin-Feng; Ching, Li-Chieh; Kou, Yu Ru; Lin, Shing-Jong; Wei, Jeng; Shyue, Song-Kun; Lee, Tzong-Shyuan
Abstract : The transient receptor potential vanilloid type 1 (TRPV1) is crucial in the pathogenesis of atherosclerosis; yet its role and underlying mechanism in the formation of macrophage foam cells remain unclear. Here, we show increased TRPV1 expression in the area of foamy macrophages in atherosclerotic aortas of apolipoprotein E-deficient mice. Exposure of mouse bone-marrow-derived macrophages to oxidized low-density lipoprotein (oxLDL) upregulated the expression of TRPV1. In addition, oxLDL activated TRPV1 and elicited calcium (Ca 2+ ) influx, which were abrogated by the pharmacological TRPV1 antagonist capsazepine. Furthermore, oxLDL-induced lipid accumulation in macrophages was ameliorated by TRPV1 agonists but exacerbated by TRPV1 antagonist. Treatment with TRPV1 agonists did not affect the internalization of oxLDL but promoted cholesterol efflux by upregulating the efflux ATP-binding cassette (ABC) transporters ABCA1 and ABCG1. Moreover, the upregulation of ABC transporters was mainly through liver X receptor α - (LXR α -) dependent regulation of transcription. Moreover, the TNF- α -induced inflammatory response was alleviated by TRPV1 agonists but aggravated by the TRPV1 antagonist and LXR α siRNA in macrophages. Our data suggest that LXR α plays a pivotal role in TRPV1-activation-conferred protection against oxLDL-induced lipid accumulation and TNF- α -induced inflammation in macrophages.